Orientation of L4 coronal tilt relative to C7 plumb line as a predictor for postoperative coronal imbalance in patients with degenerative lumbar scoliosis - Jiandang Zhang (Nature Portfolio, 2020)
Abstract The study design is case–control. To evaluate the impact of preoperative coronal patterns based on the relationship between orientation of L4 coronal tilt and C7 plumb line on immediate postoperative coronal imbalance in degenerative lumbar scoliosis (DLS) patients. Although lumbosacral fractional curve has been long stressed in correction surgery of DLS, there is paucity of literature focusing on preoperative coronal pattern based on the relationship between orientation of L4 coronal tilt and C7 plumb line and its impact on immediate postoperative coronal imbalance in DLS patients. A consecutive series of DLS patients who underwent deformity correction surgery via posterior-only approach were reviewed. According to the relationship between orientation of L4 coronal tilt and C7 plumb line preoperatively, a total of 77 DLS patients who underwent posterior spinal corrective surgery were classified into: 1. Coronal consistency pattern, L4 coronally tilts toward C7 plumb line; 2. Coronal opposition pattern, L4 coronally tilts opposite C7 plumb line. Coronal imbalance was defined as global coronal malalignment (GCM) on either side more than or equal to 20 mm. Whole-spine standing radiographs of both pattern groups were assessed preoperatively and postoperatively. There were 37 patients with coronal consistency pattern and 40 patients with coronal opposition pattern. Compared to patients with coronal opposition pattern, patients with coronal consistency pattern had significantly higher postoperative GCM (P = 0.028), lower amount of GCM correction (P = 0.013) and higher incidence of postoperative coronal imbalance (P = 0.001); further logistic regression analysis revealed coronal consistency pattern was associated with increased odds of postoperative coronal imbalance (odds ratio: 5.981; 95% confidence interval 2.029–17.633; P = 0.001). DLS patients with preoperative coronal consistency pattern carried greater risk for immediate postoperative coronal imbalance following posterior long correction surgery. Level of evidence 3